Reef fish community structure in the waters of small islands Central Bangka Regency - Adibrata, Sudirman; Adi, Wahyu; Angelia, Fera; Komarullah, Umam; Dedi, Dedi; Akbar, Arham Hafidh; Maulana, Eka; Sapriyadi, Sapriyadi; Sofyan, Sofyan; Aldia, Dia; Animah, Animah; Ayu, Citra; Gunawan, Robi; Mahatir, Muhammad; Sandri, Sandri; Evitulistiono, Rizki; Febrianto, Febrianto; Efendi, Muhammad Ichsan; Susanto, Agung; Alqodri, Muhammad Faris; Adriyansyah, Nico; Hafizah, Adisti; Ferizal, Jemi (Politeknik Negeri Sambas, 2024)
This study aimed to analyze the community structure of reef fish in the small island waters of Central Bangka. The research was conducted in March 2022 in the waters of Bebuar Island, Ketugar Island, Ketawai Island, and Gusung Asam Central Bangka Regency, Bangka Belitung Islands Province. The coral reef survey method uses purposive sampling and the coral reef fish visual census with data analysis of abundance, diversity index, uniformity, and dominance. In-site water quality measurements included six parameters: temperature, salinity, current, brightness, depth, and pH. The results showed that coral reef cover from 44.60 - 87.00% with the medium to very good category. The abundance of reef fish from 1 to 3 individuals/m2 was dominated by 18 species of the Pomacentridae family. The reef fish diversity index ranged from 2.47 to 2.90, including the medium category. The uniformity index value ranged from 0.79 - 0.94, including the high category, indicating that the species found were evenly distributed across all stations. The dominance index value ranges from 0.07 to 0.15, including low, where no species dominates significantly and the fish are evenly distributed. Temperature, brightness, pH, and salinity are factors that support the growth of coral and reef fish. A water current speed of 0.05 – 0.20 m/s is quite helpful in cleaning coral reefs from mud and can supply oxygen. Water conditions were categorized as good and fulfilled the seawater quality standards.